Reengineering of business processes of the higher school: Its prerequisites - Bogdanova A.V.; Korostelev A.A.; Shepelyuk O.L.; Rodionova A.E.; Fardeeva I.N.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper presents reengineering of business processes of the higher school. Reengineering in the framework of this article means the change in the functional structure of business processes due to the impact of various factors of the external and internal environment of the university. It is noted that the need for business process reengineering appears in each university periodically, as the processes themselves tend to minimize changes, and the requirements for the university from the outside are constantly increasing. It was concluded that the use of information technologies as the basis for the reengineering of business processes of a university allows one to streamline this process and practically eliminate or at least noticeably minimize redundant informational activities. BEIESP.